sum of 5 times of an number and 3 times of another number is63. sum of 7 times of the first number and 3 times of second number is 81. which

Question

sum of 5 times of an number and 3 times of another number is63. sum of 7 times of the first number and 3 times of second number is 81. which are the numbers?​

in progress 0
Piper 1 month 2021-08-18T19:23:45+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-18T19:24:56+00:00

    \sf{\underline{\boxed{\large{\blue{\mathsf{Solution}}}}}}

    \sf{\bold{\green{\underline{\underline{Given}}}}}

    • Sum of 5 times of a number and 3 times of a number is 63 .
    • Sum of 7 times a number and 3 times of a number is 81 .

    _______________________

    \sf{\bold{\green{\underline{\underline{To\:Find}}}}}

    • Find the original no. = ??

    ______________________

    \sf{\bold{\green{\underline{\underline{Solution}}}}}

    Let the first no. be x and second no. be y

    • Sum of 5 times of a number and 3 times of a number is 63 .

    5x + 3y = 63 ( i )

    • Sum of 7 times of a number and 3 times of a number is 81

    7x + 3y = 81 ( ii )

    • Subtracting eq ( i ) from ( ii )

    7x + 3y 5x 3y = 81 63

    2x = 18

    x = 9

    X = 9

    • putting value of x in eq i

    5 x 9 + 3y = 63

    45 + 3y = 63

    3y = 63 45

    3y = 18

    y = 6

    Y = 6

    _______________

    \sf{\bold{\green{\underline{\underline{Answer}}}}}

    • First no = 9
    • Second no = 6
    0
    2021-08-18T19:24:59+00:00

    Answer:

    first number = 9 and second number = 6

    Step-by-step explanation:

    let the first number be x and the second number be y.

    then by the given conditions we get

    5x + 3y = 63 ( first equation )

    7x + 3y = 81 ( second equation)

    subtracting the second equation with the first equation we get:

    2x = 18

    x = 18/2 = 9

    x = 9

    substitute x = 9 in first equation :

    (5 × 9) + 3y = 63

    45 + 3y = 63

    3y = 63 – 45 = 18

    3y = 18

    y = 18/3 = 6

    y= 6

    therefore the first number(x) = 9

    the second number(y) = 6

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )